Characterization of the First W-Specific Protein-Coding Gene for Sex Identification in Helicoverpa armigera - Deng, Zhongyuan; Zhang, Yakun; Zhang, Min; Huang, Jinyong; Li, Changyou; Ni, Xinzhi; Li, Xianchun (Frontiers in Genetics, 2020)
Helicoverpa armigera is a globally-important crop pest with a WZ (female) / ZZ (male) sex chromosome system. The absence of discernible sexual dimorphism in its egg and larval stages makes it impossible to address any sex-related theoretical and applied questions before pupation unless a W-unique sequence marker is available for sex diagnosis. To this end, we used one pair of morphologically pre-sexed pupae to PCR-screen 17 non-transposon transcripts selected from 4855 W-linked candidate reads identified by mapping a publically available egg transcriptome of both sexes to the male genome of this species and detected the read SRR1015458.67499 only in the female pupa. Subsequent PCR screenings of this read and the previously reported female-specific RAPD (random amplified polymorphic DNA) marker AF18 with ten more pairs of pre-sexed pupae and different annealing positions and/or temperatures as well as its co-occurrence with the female-specific transcript splicing isoforms of doublesex gene of H. armigera and amplification and sequencing of their 5’ unknown flanking sequences in three additional pairs of pre-sexed pupae verified that SRR1015458.67499 is a single copy protein-coding gene unique to W chromosome (named GUW1) while AF18 is a multicopy MITE transposon located on various chromosomes. Test application of GUW1 as a marker to sex 30 neonates of H. armigera yielded a female/male ratio of 1.14 : 1.00. Taken together, GUW1 is not only a reliable DNA marker for sexing all stages of H. armigera, but also represents the first W-unique protein-coding gene in lepidopterans.